2022
DOI: 10.1007/s10964-022-01684-4
|View full text |Cite
|
Sign up to set email alerts
|

School-based Mental Health Interventions Targeting Depression or Anxiety: A Meta-analysis of Rigorous Randomized Controlled Trials for School-aged Children and Adolescents

Abstract: Past meta-analyses in mental health interventions failed to use stringent inclusion criteria and diverse moderators, therefore, there is a need to employ more rigorous methods to provide evidence-based and updated results on this topic. This study presents an updated meta-analysis of interventions targeting anxiety or depression using more stringent inclusion criteria (e.g., baseline equivalence, no significant differential attrition) and additional moderators (e.g., sample size and program duration) than prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 93 publications
0
28
0
1
Order By: Relevance
“…Universally delivered psychosocial interventions, especially those based on interpersonal skills training, emotional regulation, alcohol, drug and lifestyle education, can improve youth mental health and reduce risky behaviors. Randomized controlled tri als showed that, compared to control groups, school-based interventions have a significant positive effect on symptoms of depression and anxiety, suicide attempts, and suicidal ideation 10,11 .…”
Section: Improving Mental Health Through Fostering Healthy Lifestyles...mentioning
confidence: 99%
“…Universally delivered psychosocial interventions, especially those based on interpersonal skills training, emotional regulation, alcohol, drug and lifestyle education, can improve youth mental health and reduce risky behaviors. Randomized controlled tri als showed that, compared to control groups, school-based interventions have a significant positive effect on symptoms of depression and anxiety, suicide attempts, and suicidal ideation 10,11 .…”
Section: Improving Mental Health Through Fostering Healthy Lifestyles...mentioning
confidence: 99%
“…In contrast to the results by Caldwell and colleagues, an update of the meta‐analysis on school‐based anxiety and depression interventions for primary and secondary education using more stringent inclusion criteria (e.g. only including randomized controlled trials, quantitative outcomes) did show effectiveness on children's levels of anxiety with small effects (Zhang, Wang, & Neitzel, 2023). Also for children with externalizing problems, there are interventions with an evidence base, including behavioral teacher training for primary school children (also see Staff, 2022) and interventions focused on planning and organizational skills for children in secondary education.…”
Section: Lack Of Evidence Of Effectivenessmentioning
confidence: 75%
“…A good example of how to investigate which elements of school-based interventions work for whom is a randomized controlled microtrial into different techniques of a brief teacher training for primary school-aged children with impairing levels of inattention, hyperactivity and/ or impulsivity (Staff et al, 2021) are effective in reducing the child's behavioural problems, and also showed that specific moderators, such as class size, age of the child and the child's cognitive performances influenced intervention outcomes. Another example is the abovementioned meta-analysis by Zhang et al (2023) which showed that to decrease anxiety and depression, targeted interventions are more effective than universal programs, interventions were more effective in secondary compared to primary education and cognitive behavioural interventions were more effective than other interventions, while the length of the intervention did not matter. More studies like this are needed to be able to take decisions on how to allocate the limited resources and personalize interventions to the school setting and the child.…”
Section: What Work For Whom Under Which Circumstances: a Brief Resear...mentioning
confidence: 99%
“…However, inaccessibility to school-based mental health services is a plausible mediating factor for the changes in ED mental health visits that we observed. Results from recent meta-analyses suggest that school-based services are effective in reducing depression and anxiety symptoms 26 and that programs for at-risk children can reduce psychological stress symptoms 27 . Children seeking emergency mental health care may be the children these programs are most effective and tailored for.…”
Section: Discussionmentioning
confidence: 99%